Dual-weighted goal-oriented adaptive finite elements for optimal control of elliptic variational inequalities∗. (7th April 2014) - Hintermüller, M.; Hoppe, R.H.W.; Löbhard, C.
<x content-type="archive" xml:space="preserve">Abstract</x> A dual-weighted residual approach for goal-oriented adaptive finite elements for a class of optimal control problems for elliptic variational inequalities is studied. The development is based on the concept of C-stationarity. The overall error representation depends on primal residuals weighted by approximate dual quantities and vice versa as well as various complementarity mismatch errors. Also, a priori bounds for C-stationary points and associated multipliers are derived. Details on the numerical realization of the adaptive concept are provided and a report on numerical tests including the critical cases of biactivity are presented.